2013
DOI: 10.3389/fmicb.2013.00022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated application of sulfadiazine-contaminated pig manure on the abundance and diversity of ammonia and nitrite oxidizers in the root-rhizosphere complex of pasture plants under field conditions

Abstract: In a field experiment, the impact of repeated application of the antibiotic sulfadiazine (SDZ)-contaminated pig manure was assessed on functional microbial communities involved in ammonia and nitrite oxidation in the root-rhizosphere complexes (RRCs) of diverse plants composing a pasture. We surveyed the abundance of ammonia-oxidizing archaea (AOA) and bacteria (AOB) as well as Nitrobacter- and Nitrospira-like nitrite-oxidizing bacteria (NOB) by quantitative PCR (qPCR), and the diversity of amoA AOA and Nitrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 56 publications
(61 reference statements)
2
17
0
Order By: Relevance
“…Only archaea were not affected by the different forms of tillage management. The latter observation, which is in accordance to our initial hypothesis, can be most likely explained by the dominance of ammonia oxidizers in most upland soils, which are very stable in response to shifts in environmental conditions which has been shown in a large number of studies including the effects of antibiotics (Schauss et al 2009), land use intensity (Bru et al 2011;Meyer et al 2013) or heavy metal content (Ollivier et al 2013). Only at the sites, where a strong SOC accumulation might be expected in response to shifts in tillage management, archaea might also be affected, as a result of the autotrophic lifestyle of ammonia oxidizers, which has been recently shown by Souza et al (2013) using a metagenomic approach.…”
Section: Dynamics Of Microbial Communitiessupporting
confidence: 59%
“…Only archaea were not affected by the different forms of tillage management. The latter observation, which is in accordance to our initial hypothesis, can be most likely explained by the dominance of ammonia oxidizers in most upland soils, which are very stable in response to shifts in environmental conditions which has been shown in a large number of studies including the effects of antibiotics (Schauss et al 2009), land use intensity (Bru et al 2011;Meyer et al 2013) or heavy metal content (Ollivier et al 2013). Only at the sites, where a strong SOC accumulation might be expected in response to shifts in tillage management, archaea might also be affected, as a result of the autotrophic lifestyle of ammonia oxidizers, which has been recently shown by Souza et al (2013) using a metagenomic approach.…”
Section: Dynamics Of Microbial Communitiessupporting
confidence: 59%
“…For example, the partitioning of NH 4 + between soil surfaces and solution could regulate solution-phase levels and therefore influence nitrifier activity and NH 3 toxicity 15 . Simultaneous quantification of genes associated with activities of NOB, AOB and NH 4 + oxidizing archaea in soil following amendment with N has been reported in a few studies 16 17 18 , but more data are needed to understand the role of nitrifier responses in regulating NO 2 − and N 2 O dynamics. Limited understanding of these and other factors limits our ability to predict NO 2 − dynamics for a particular soil, management practice, or climate condition, and our ability to predict N 2 O emissions resulting from NO 2 − transformations 19 20 .…”
mentioning
confidence: 99%
“…For example, anyone can get more nutrients and living space in a given medium will certainly function as a dominant member in the microcosm. Several previous studies showed those spatial niche differentiation patterns of a functionally redundant organisms often co‐exist at the same spatial scale , or differ in their spatial distribution .…”
Section: Discussionmentioning
confidence: 99%